Preventive effects of silymarin extract on carbon tetrachloride-induced hepatotoxicity in broilers - mohammadreza Mohammadi Malayeri; abolfazl Dadkhah Tehrani; amir Rezaei (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2014)
It has been proved that Silymarin is effective in prevention and treatment of human liver diseases such as cirrhosis. Therefore, the objective of this study was to evaluate the preventive effects of Silymarin extract as a food additive on hepatotoxicity induced by carbon tetrachloride in broilers. Ninety broiler chickens were randomly assigned to 9 equal study groups as follow: negative control, positive control which were injected 2ml/kg BW (body weight) ccl4 dissolved  in olive oil (1:1) via IP  in the 24th and 26th days, olive oil control, treatment controls which were receiving 3,6 and 10 mg/kg BW silymarin in 1ml olive oil respectively by gavage from the 21st up to 26th days  and treatment groups which received ccl4 and  3,6 and 10 mg/kg BW silymarin extract respectively. Blood and liver samples were collected to assay ALT, AST and ALP activities as well as pathological changes. The Data were analyzed using ANOVA method by SPSS. The results revealed that carbon tetrachloride significantly increased ALT,AST and ALP activities in comparison with the negative control group (p